Routine radiographic follow-up is not necessary after physeal fractures of the distal tibia in children - Stenroos, Antti; Kosola, Jussi; Puhakka, Jani; Laaksonen, Topi; Ahonen, Matti; Nietosvaara, Yrjänä (Acta Orthopaedica, 2019)
Background and purpose — Unnecessary radiographic and clinical follow-ups are common in treatment of pediatric fractures. We hypothesized that follow-up radiographs are unnecessary to monitor union of physeal fractures of the distal tibia. Patients and methods — All 224 (147 boys) children under 16 years old treated for a physeal fracture of the distal tibia during a 5-year period (2010–14) in Helsinki Children’s Hospital were included in this study. Peterson type II fractures comprised 55% and transitional fractures (Tillaux and Triplane) 20% of all injuries. Fracture displacement and alignment was measured. Type and place of treatment was recorded. Number of follow-up radiographs and outpatient visits was calculated and their clinical significance was assessed. Results — 109 children had fractures with < 2 mm displacement and no angulation. The other 115 children’s mean fracture displacement was 6 mm (2–28). 54% of all children were treated by casting in situ in the emergency room, 20% with manipulation under anesthesia and 26% with surgery (internal 57, external fixation 2). Median 3 (1–7) follow-up appointments and median 3 (0–6) radiographs were taken. Follow-up radiographs at or before cast removal did not alter treatment in any of the patients. 223 patients’ fractures healed within 4–9 weeks in good alignment (≤ 5° angulation). Interpretation — Routine radiographic follow-up is unnecessary to monitor alignment and union of physeal fractures of the distal tibia.